Amelioration of ammonia-induced intestinal oxidative stress by dietary Clostridium butyricum in giant freshwater prawn (Macrobrachium rosenbergii). Issue 131 (December 2022) - Sun, Cunxin; Tadese, Dawit Adisu; Wangari, Muritu Rebecca; Zhou, Qunlan; Zheng, Xiaochuan; Liu, Bo; Tamiru, Metekia; Dagne, Adamneh; Janssens, Geert Paul Jules; Zhao, Yongfeng
Abstract: The use of Clostridium butyricum in crustacean aquaculture for anti-abiotic stress is yet unknown. Feeds were formulated containing 0, 125, 250, 500, and 1000 mg/kg Clostridium butyricum (2 × 10 7 CFU/g), respectively. The giant freshwater prawns ( Macrobrachium rosenbergii ) were fed for 8 weeks in triplicate. The results showed that C. butyricum- supplemented groups improved growth performance significantly with the optimum level at 610 mg/kg. Ammonia stress reduced hemolymph glucose, total protein, total cholesterol, and triglyceride concentrations while dietary C. butyricum significantly increased hemolymph glucose and total protein levels after the ammonia challenge. Ammonia stress increased inducible nitric oxide synthase (iNOS) and nitric oxide (NO) levels, and the treatments supplemented with C. butyricum had considerably enhanced levels of iNOS and NO after stress. Treatment with C. butyricum increased the level of superoxide dismutase (SOD), and decreased the level of malondialdehyde (MDA) and superoxide anion, with the 125 mg/kg treated groups having the extreme value. Furthermore, C. butyricum -treated groups reduced the expression of HSPs after ammonia stress while the ammonia stress induced the expression of HSP60, HSP70, and HSP90. Dietary C. butyricum elevated the expression of peroxiredoxin-5 and toll in response to ammonia stress. The results indicate that dietary supplementation with 125–500 mg/kg of C. butyricum (2 × 10 7 CFU/g) improved biochemical and antioxidant features as well as intestinal immunity of M. rosenbergii under ammonia challenge by activating the toll signal pathway. Highlights: The optimum level of dietary C. butyricum is 615 mg/kg in M. rosenbergii. Dietary C. butyricum improves the resistance to ammonia stress of M. rosenbergii. C. butyricum relieves ammonia-induced intestinal oxidative stress of M. rosenbergii. Heat-shock proteins and toll pathway partly control the intestinal oxidative stress.